(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the study of the institution of evidence and substantiation in the administrative process, the content of some norms of the Code of Civil Procedure of Ukraine, which regulate the process of substantiation and the features of the use of evidence, is analyzed. The article supports the scientific position of scientists that the institution of evidence and substantiation is an integral part of the internal system of any procedural branch of law, because the law regulates social relations that mediate the procedure for establishing the presence or absence of circumstances that are important for resolving the case. With the help of the legal mechanism of this institution, a clear phasing of evidentiary activity is ensured, as well as compliance of the procedural form of evidence with the requirements established by law. It is proved that substantiation is an activity of subjects of substantiation regulated by administrative and procedural norms, aimed at collecting, submitting, evaluating, reviewing the provision, researching, requesting or temporarily removing evidence for the purpose of objective truth and fair resolution of a public-legal dispute.